Dampak Penggunaan Sosial Media pada Anak dan Remaja di RT 04 Kelurahan Nusa Indah - Yuliana, Vinna; Andhyta, Chairani; Burenza, Fardho; Burhanifah, Burhanifah; Endang, Anis (Universitas Dehasen Bengkulu, 2024)
The development of technology has had an impact on changes in the play patterns of children and adolescents, where the majority prefer to play gadgets, especially social media, at home rather than playing with peers outside the home. This is also seen in RT 04 of Nusa Indah Village. The use of social media by children and adolescents has a significant impact on various aspects of their lives. One of the positive impacts is the creation of opportunities to broaden horizons and knowledge. Meanwhile, the negative impacts are digital addiction, reduced physical activity time, and minimal social interaction in the real world. In addition, exposure of children and adolescents to inappropriate content can trigger mental health issues and undesirable behaviors. Therefore, it is important to thoroughly understand how interactions with social media can shape behavior patterns and mental health of children and adolescents. This community service conducted in RT 04 is expected to provide education related to the use of social media. By digging deeper into the positive and negative impacts of social media use on early childhood and adolescence in RT 04 Nusa Indah Village, this service is expected to be the basis for designing more targeted and effective policies and intervention programs to support the development of a healthy young generation in this digital era.